The use of implicit persuasion in decision-making about treatment for end-stage kidney disease. Issue 4 (July 2022) - van Dulmen, Sandra; Peereboom, Emma; Schulze, Lotte; Prantl, Karen; Rookmaaker, Maarten; van Jaarsveld, Brigit C; Abrahams, Alferso C; Roodbeen, Ruud
Background: There are various options for managing end-stage kidney disease. Each option impacts the lives of patients differently. When weighing the pros and cons of the different options, patients' values, needs and preferences should, therefore, be taken into account. However, despite the best intentions, nephrologists may, more or less deliberately, convey a treatment preference and thereby steer the decision-making process. Being aware of such implicit persuasion could help to further optimise shared decision-making (SDM). This study explores verbal acts of implicit persuasion during outpatient consultations scheduled to make a final treatment decision. These consultations mark the end of a multi-consultation, educational process and summarise treatment aspects discussed previously. Methods: Observations of video-recorded outpatient consultations in nephrology ( n = 20) were used to capture different forms of implicit persuasion. To this purpose, a coding scheme was developed. Results: In nearly every consultation nephrologists used some form of implicit persuasion. Frequently observed behaviours included selectively presenting treatment options, benefits and harms, and giving the impression that undergoing or foregoing treatment is unusual. The extent to which nephrologists used these behaviours differed. Conclusion: The use of implicit persuasion while discussing different kidney replacement modalities appears diverse and quite common. Nephrologists should be made aware of these behaviours as implicit persuasion might prevent patients to become knowledgeable in each treatment option, thereby affecting SDM and causing decisional regret. The developed coding scheme for observing implicit persuasion elicits useful and clinically relevant examples which could be used when providing feedback to nephrologists.